Analisis Perbandingan Python dan C++ dalam Menyelesaikan Sistem Persamaan Linear menggunakan Metode Gauss Seidel - Mutiara Azhara; Tiara Khairani; Ita Margaretta Br Tarigan (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
A linear equation system is one of the fundamental problems in computational mathematics that is widely applied in various fields of science and engineering. Numerical solution of linear equation systems using iterative methods, particularly the Gauss-Seidel method, provides high efficiency for large-dimensional systems. This study aims to analyze and compare the performance of Python and C++ programming languages in implementing the Gauss-Seidel method to solve linear equation systems of order 3×3, 4×4, and 5×5. The research is of a quantitative comparative nature with comparison variables including computation time, number of iterations, memory usage, and accuracy level. The results show that C++ has a significant advantage in computation time, with an average speed 32.9 times faster than Python. For a 3×3 system, Python requires 2.341 ms while C++ only needs 0.089 ms. For a 5×5 system, Python requires 9.156 ms while C++ requires 0.251 ms. For the number of iterations and numerical accuracy, both languages produce equivalent values because they use the same algorithm with an error tolerance of 10⁻⁶. Python’s memory usage is on average 9.5 times greater than C++. The study concludes that C++ is superior in computational efficiency, while Python offers greater ease of development and programming productivity. The choice of programming language should be tailored to the application’s requirements, whether prioritizing execution speed or ease of implementation.